Complexation of U(Ⅵ) with Dialkyldithiophosphinic Acid - SUI Qiaorui1, XIA Tiantian1, DENG Qin1, LAN Youshi1, YANG Suliang1, TIAN Guoxin1,2 (Yuanzineng kexue jishu, 2024)
The complexation of U(Ⅵ) with two dialkyldithiophosphinic acids, bis(2,4,4-trimethylpentyl) dithiophosphinic acid (HA) and bis(2-methylpropyl)-dithiphosphinic acid (HL) was investigated by slope analysis method and X-ray diffraction method in solid compound along with Raman spectroscopy. In the solvent extraction system using HA in xylene as organic phase and U(Ⅵ) in 1.0 mol/L NaNO3 as aqueous phase, two extracted complexes of U(Ⅵ) are recognized in the organic phase by the slope analysis of the dependence of the distribution ratio on the concentration of HA in the organic phase and the pH in the aqueous phase, by Raman spectroscopy it is found that in one extracted complex formed in the organic phase with relatively low U(Ⅵ) loading but excessive free HA there is no water molecule coordinated with U(Ⅵ), while in the other one formed with relatively high U(Ⅵ) loading but less free HA in the organic phase there is one water molecule bonding to U(Ⅵ). By comparing the similarity and difference between the Raman spectra of the extracted complexes in the organic phase and the two solid U(Ⅵ) complexes with HL, UO2L2·H2O and UO2L3·(CH3)2NH2·H2O, along with analyzing their structures the extracted complexes are speculated to be UO2A2·HA and UO2A2·H2O, respectively. Solid compound UO2L2·H2O was prepared by slow evaporation method from kerosene solution equilibrated with an aqueous solution of same volume containing 1∶2 of U(Ⅵ) to L-. It is crystalized in I2/a space group with unit cell: a＝8.606 6(2) Å, b＝20.916 6(3) Å, c＝15.184 7(3) Å; α＝90°, β＝105.337(2)°, γ＝90°; Z＝4. In UO2L2·H2O complex, two bidentate L- providing totally four sulfur atoms along with one oxygen from the water molecule coordinate with U(Ⅵ) in the equatorial plane to form a typical pentagonal bipyramid structure. The other solid compound UO2L3·(CH3)2NH2·H2O was obtained directly from aqueous solution containing 1∶3 of U(Ⅵ) to (CH3)2NH2L by slow evaporation. It is crystalized in P-1 space group with unit cell: a＝12.450(2) Å, b＝13.632(2) Å, c＝13.863(2) Å; α＝74.274(13)°, β＝79.896(14)°, γ＝67.443(15)°; Z＝2. In the solid compound UO2L3·(CH3)2NH2·H2O, three L- ligands are in different coordination modes, two of the three L- as bidentate and one as mono-dentate coordinate with U(Ⅵ) in the equatorial plane totally providing five sulfur atoms to form a pentagonal bipyramid structure, while the water molecule does not bond to U(Ⅵ) but associates with (CH3)2NH+2 anion to contribute to the crystal lattice.